Pakistan Army Green Book : Year of the Junior Leaders, 1990 - Pakistan Army; Editorial Board : Jamil Qudrat Warsi, Muhammad ; Shabraz Abbasi, Muhammad and Ishfaq Ali, Syed (Rawalpindi, Pakistan Pakistan Army, 1990)
The views expressed in this book are those of the authors and not to be taken as the official opinion or policies of the General Headquarters
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals